Sealing versus Nonsealing: Cost-benefit analysis - Anshula N Deshpande; Rameshwari Yashpalsinh Raol; Urvashi Sudani; Neelam Joshi; Neha Pradhan (Wolters Kluwer Medknow Publications, 2016)
Dental caries still remains the second most prevalent disease after common cold, out of which occlusal caries is the most profound one. In India, more than 40% of children are found to be affected by dental caries. Occlusal surfaces of the teeth are most susceptible sites for caries development due to their morphology. They are least benefited from fluoride application. Various efforts have been made by the preventive means to decline the rate of caries, one of which being sealant application. Sealants have come into existence long back since 1971 when first pit and fissure sealant Nuva-Caulk came into existence. There have been piles of literature stating the benefits that arrive from sealing the teeth. However, one crucial point that is being missed most of the times is the cost-effectiveness of the sealant. There are various schools of thoughts, regarding this that is controversial ones. Some of the analysts believe that always sealing may be a bit costlier, but it reduces subsequent dental treatments and hence saves money as well as time. However, some believe that why to unnecessarily seal the teeth in all cases even when the child is not at a risk to develop caries. Hence, we need to foresee both the sides of equation. For best clinical practice and decision-making, we need to have a balance of best evidence, clinical judgment, and the most important, patient needs and preferences.